2019
DOI: 10.1108/nbri-11-2018-0070
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of the impact of goal orientation on individual ambidexterity – moderating roles of goal interdependence and constructive controversy

Abstract: Purpose Ambidexterity is the source of organizational sustainable development and long-term success. However, understanding the role of individual ambidexterity in organizations remains underdeveloped. Recently, scholars have increasingly emphasized the importance of individual ambidexterity, calling for more research on the topic. This study aims to explore the factors influencing individual ambidexterity. It proposed that goal orientation would be related to individual ambidexterity, and perceived cooperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 58 publications
2
16
0
Order By: Relevance
“…A longer period of time might have shown a different outcome as team members developed increased knowledge about each other [ 40 ]. Although the results aligned with studies detecting a direct association between swift trust and creativity on teams [ 7 , 10 , 11 , 12 ], those studies had assessed swift trust as one variable rather than as two separate components. Therefore, the results support findings that cognition-based trust plays a larger role than affect-based trust in forming and maintaining swift trust on short-term teams [ 5 , 28 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…A longer period of time might have shown a different outcome as team members developed increased knowledge about each other [ 40 ]. Although the results aligned with studies detecting a direct association between swift trust and creativity on teams [ 7 , 10 , 11 , 12 ], those studies had assessed swift trust as one variable rather than as two separate components. Therefore, the results support findings that cognition-based trust plays a larger role than affect-based trust in forming and maintaining swift trust on short-term teams [ 5 , 28 ].…”
Section: Discussionsupporting
confidence: 72%
“…Generally, team trust and team creativity have been directly correlated [ 7 , 10 , 11 , 12 ]. However, the association between conflict and creativity in team settings has been less straightforward, and it varies with the type of conflict in question.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of individual ambidexterity that explicitly indicate some theoretical framework are mainly based on micro- or psychological theories, such as cognitive dissonance and evaluation theory (Bonesso et al, 2014), social cognitive theory (Xiang et al, 2019), social exchange theory (Caniëls et al, 2017), neuroscience literature (Laureiro-Martínez et al, 2015), behavioral complexity theory (Keller & Weibler, 2015), regulatory mode and focus theories (Jasmand et al, 2012), self-determination theory (Garcia et al, 2019), social identity theory (Luu et al, 2018), or the theory of planned behavior (Yu et al, 2018), among others.…”
Section: Resultsmentioning
confidence: 99%
“…Only one paper measures individual ambidexterity from a continuum (1- to 5-point scale) with the intermediate value (3) reflecting ambidexterity (Rogan & Mors, 2014), and Yeganegi et al (2019) use a dichotomous variable. Regarding the way the construct of individual ambidexterity is operationalized from the two dimensions studied, the way that predominates is the interaction or multiplication of the two variables to obtain the individual ambidextrous measure (e.g., Li et al, 2015; Mom et al, 2015; Schultz et al, 2013; Torres et al, 2015), although there are also papers that use balance (subtraction) (Caniëls & Veld, 2019; De Visser & Faems, 2015; Keller & Weibler, 2015), addition (Caniëls et al, 2017; Prieto-Pastor & Martin-Perez, 2015 ; Xiang et al, 2019), or combine several measures (Lee & Lee, 2016; Rosing & Zacher, 2017; P. Sok & O’Cass, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The literature on ambidexterity defines individual ambidexterity as a "behavioural orientation towards combining exploration and exploitation, related activities within a certain period of time" [88], so that "individuals engage in exploration while carrying on exploitation by allocating time and resources between the two different activities" [89] (p. 467). Activities related to individual ambidexterity have been widely recognised as beneficial to individuals, and empirical results have shown that this ambidexterity enriches employees' jobs, promotes their creativity, and thus their performance [88].…”
Section: Individual Ambidexterity In the Technology Transfer Officesmentioning
confidence: 99%